2004
DOI: 10.1002/art.20434
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular events in platelet activation induced by antiphospholipid antibodies in the presence of low doses of thrombin

Abstract: Objective. Thrombosis and thrombocytopenia are features of the antiphospholipid syndrome (APS), suggesting that antiphospholipid antibodies (aPL) may bind platelets, causing activation and aggregation of platelets and thrombosis. The intracellular events involved in aPL-mediated platelet activation are not fully understood and are therefore the subject of this study.Methods. IgG fractions and their F(ab) 2 fragments were purified from the sera of 7 patients with APS and from the pooled sera of 10 healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
102
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 40 publications
12
102
2
2
Order By: Relevance
“…These processes are triggered by the interaction of pathogenic aPL with monocytes, endothelial cells (EC), platelets, trophoblast and endometrial cells, as well as plasma components of the coagulation cascade. 16,17,[26][27][28] Therefore, understanding the proposed hypothesis would stand for a growing evidence for the importance of placental apoptosis through TLRs in the pathogenesis of aPL-mediated pregnancy loss. Pathogenic aPL bind to phospholipid binding proteins of which β2GPI is the best characterized.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are triggered by the interaction of pathogenic aPL with monocytes, endothelial cells (EC), platelets, trophoblast and endometrial cells, as well as plasma components of the coagulation cascade. 16,17,[26][27][28] Therefore, understanding the proposed hypothesis would stand for a growing evidence for the importance of placental apoptosis through TLRs in the pathogenesis of aPL-mediated pregnancy loss. Pathogenic aPL bind to phospholipid binding proteins of which β2GPI is the best characterized.…”
Section: Discussionmentioning
confidence: 99%
“…3 To this end, pre-TCR signaling may result in the arrest of pT␣ and the triggering of TCR␣ transcription. This, together with the higher pairing efficiency of TCR␤ with TCR␣ rather than with pT␣, may finally favor the switch from pre-TCR to the ␣␤TCR expression, thus sustaining differentiation progression.…”
Section: Cms Links the Tail -----------------------------------------mentioning
confidence: 99%
“…For example, in experimental autoimmune encephalomyelitis (a model of multiple sclerosis), it has been shown that the order of epitope spreading can be a consistent and predictable process. 2,3 In this issue of Blood, Hall and colleagues have expanded this question to AIHA, using a murine model in which NZB mice spontaneously generate autoantibodies against Band 3. To test whether AIHA requires Band 3 to occur, Hall and colleagues monitored the development of AIHA in NZB mice with a deletion of the Band 3 gene.…”
mentioning
confidence: 99%
“…Recently, some of the intracellular pathways activated by APL antibodies in platelets, monocytes and endothelial cells have been examined. Studies have conclusively shown that APL antibodies induce phosphorylation of p38 mitogen-activated protein kinase (p38 MAPK) in platelets, monocytes and endothelial cells, and activate the transcriptional factor nuclear factor-kappa B (NF-jB) in monocytes and endothelial cells [1][2][3][4][5].Although there is convincing evidence that APL antibodies can stimulate endothelial cells, monocytes and platelets, relatively little is known about the cell surface receptors that are engaged or crosslinked to induce intracellular signaling. In endothelial cells, there is indirect evidence that annexin A2, a receptor for tissue plasminogen activator (t-PA) and plasminogen, and toll-like receptor 4 (TLR-4), a receptor for bacterial lipopolysaccharide (LPS), may be binding b 2 -GPI and triggering intracellular signaling.…”
mentioning
confidence: 99%
“…Recently, some of the intracellular pathways activated by APL antibodies in platelets, monocytes and endothelial cells have been examined. Studies have conclusively shown that APL antibodies induce phosphorylation of p38 mitogen-activated protein kinase (p38 MAPK) in platelets, monocytes and endothelial cells, and activate the transcriptional factor nuclear factor-kappa B (NF-jB) in monocytes and endothelial cells [1][2][3][4][5].…”
mentioning
confidence: 99%